To find the zeros of the function \( g(x) = x^2 - 3x - 10 \), we need to set the function equal to zero and solve for \( x \):
\[ x^2 - 3x - 10 = 0 \]
Next, we can factor the quadratic. We are looking for two numbers that multiply to \(-10\) (the constant term) and add to \(-3\) (the coefficient of the linear term). The numbers \(-5\) and \(2\) fit this condition:
\[ x^2 - 5x + 2x - 10 = (x - 5)(x + 2) = 0 \]
Thus, the factors are \( (x - 5) \) and \( (x + 2) \). Setting each factor to zero gives us the zeros:
- \( x - 5 = 0 \) → \( x = 5 \)
- \( x + 2 = 0 \) → \( x = -2 \)
So, the zeros are \( x = 5 \) and \( x = -2 \).
Based on the stated options, the correct statement is:
the zeros are 5 and -2, because the factors are x - 5 and x + 2.